KUALITAS HADIS “MAN JARRA TSAUBAHU” STUDI KRITIK SANAD DAN MATAN HADIS - Muhammad Nasir (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2021)
This research examines the quality of the traditions "manjara tsaubahu", that they explain the prohibition of lengthening cloths or pants with arrogant intentions, whether it is being arrogant to Allah or to others, being arrogant to Allah is where when you are worshiping Allah. Then the hadiths use several kinds of commands in terms of prohibitions, including; By threatening to be reluctant by Allah, there are also those who do not accept their worship (do not get rewarded) and so on. So that if we lengthen cloths or pants with arrogant intentions, it is prohibited by Allah. The main focus in this research is the sanad and observations of the Prophet's hadiths which contain the "manjaara tsaubahu". This research is library research with the main reference being the books of the hadiths of al-Kutub al-Tis'ah and maktabah syamilah. Besides the hadith books mentioned above, books related to takhrij al-hadith are also references in this study, such as: Ushul al-Takhrij wa Dirasat al-Asanid. Research methodology of the Prophet's hadith written by Syuhudi Ismail, and others. To examine the narrators of Hadith, the books that are used as references are related to the observational study of hadith. The result of this research is the authentic quality hadith sanad, namely the history of Abu Dawud. From the eyes of the hadith, the quality of authenticity does not contradict the Qur'an and authentic traditions, common sense, historical facts, language and with Islamic principles.